The Mutations Associated with Dilated Cardiomyopathy. (22nd May 2012) - Parvari, Ruti; Levitas, Aviva
Abstract : Cardiomyopathy is an important cause of heart failure and a major indication for heart transplantation in children and adults. This paper describes the state of the genetic knowledge of dilated cardiomyopathy (DCM). The identification of the causing mutation is important since presymptomatic interventions of DCM have proven value in preventing morbidity and mortality. Additionally, as in general in genetic studies, the identification of the mutated genes has a direct clinical impact for the families and population involved. Identifying causative mutations immediately amplifies the possibilities for disease prevention through carrier screening and prenatal testing. This often lifts a burden of social isolation from affected families, since healthy family members can be assured of having healthy children. Identification of the mutated genes holds the potential to lead to the understanding of disease etiology, pathophysiology, and therefore potential therapy. This paper presents the genetic variations, or disease-causing mutations, contributing to the pathogenesis of hereditary DCM, and tries to relate these to the functions of the mutated genes.